Assessment of the informed consent process in the provision of dental care in Mulago hospital, Uganda - David Nono; Edward Mapley; Charles Mugisha Rwenyonyi; Isaac Okullo (BMC Oral Health, 2022)
Abstract Background Informed consent is grounded in the principle of autonomy and represents patients’ right to participate in clinical decisions regarding their treatment. It is equally an ethical and legal requirement in dental care. The dental practitioner must offer appropriate information about all aspects of the treatment and ensure that a patient understands and makes an informed decision. There is limited literature on informed consent for dental care in Uganda. This study assessed patients’ comprehension of the informed consent process and dental practitioners’ practices in obtaining informed consent. Methods This was a cross-sectional descriptive study conducted in the Dental Outpatient Department of Mulago Hospital. Two separate questionnaires were employed to collect data from dental patients and dental practitioners, respectively. Data were entered into Epi-data, coded, and imported into STATA 14 for statistical analysis. Results Overall, the level of patients’ comprehension of the informed consent process was 91.1%, with 96.3% who felt the dental practitioners satisfactorily explained to them the treatment received and, 65.1% understood very well the information given to them. About 93.5% of the patients confessed that they were given other options of treatment while 98.5% consented before the dental practitioners started treatment. Most dental practitioners 94.7% followed good clinical practices in obtaining informed consent and 98.7% gave information before initiation of treatment while 85.3% obtained consent from patients before starting any procedures. However, only 5.3% of the dental practitioners obtained written informed consent from patients. Conclusion There is a need to devise ways of improving patients’ understanding of the treatment information given to them to support them make better and informed decisions regarding their care. Dental practitioners need to put more emphasis on the use of written consent in dental care because documentation helps in providing accountability and protects dentists from medical litigation in case the patients were to sue them for any treatment-related complications.